A general framework for modifying health-relevant behavior: reducing undergraduate binge drinking by appealing to commitment and reciprocity - Conner, Amy E. (Kansas State University, 2005)
Binge drinking is a serious health problem among American college students (Wechsler, Lee, Kuo, & Lee, 2000a). One technique that may reduce binge drinking is compliance. Cialdini (2001) defined compliance as taking an action because it has been requested and described sequential request tactics, including the commitment/consistency-based foot-in-the-door (FITD) tactic, and the reciprocity-based door-in-the-face (DITF) tactic. Cialdini claimed that these tactics yield automatic compliance. The present research investigated Cialdini’s automaticity assumption within the context of reducing binge drinking, by including a neutral or weak message along with the compliance request (consistent with Brannon & Brock, 2001). The main hypothesis was that compliance is not automatic, as demonstrated by differential compliance consistent with message strength. Parallel experiments investigated compliance with requests to reduce one’s drinking behavior (Experiment 1, N=129) or communicate about responsible drinking (Experiment 2, N=122). Participants were randomly assigned to one of six conditions in each experiment. Consistent with the purpose of each experiment, participants indicated whether they would comply with initial requests consistent with FITD and DITF methodology, or were not asked to comply with an initial request (control); read either a neutral or weak message about the importance of moderate alcohol consumption; then responded to the target request (dependent variable) by reporting the likelihood that they would not drink excessively for one week (Experiment 1) or would discuss responsible drinking with someone (Experiment 2). Participants in both experiments completed demographic and alcohol consumption information and a social desirability measure (Strahan & Gerbasi, 1972). Data were submitted to 2(Strength) × 3(Appeal) × 2(Gender) ANCOVAs (drinks per occasion and social desirability were covariates). Experiment 1 revealed a significant Strength × Appeal interaction, with the DITF and FITD appeals eliciting lower compliance rates than the control appeal when accompanied by a weak persuasive message, thereby refuting Cialdini’s automaticity assumption. A significant main effect for appeal in Experiment 2 (DITF yielded lower compliance than FITD or control appeal) did not support Cialdini’s (2001) claim. Correlates of drinking behavior among college students are discussed, as are implications of the present research for compliance theory and reducing binge drinking on American college campuses.
Keywords: Compliance; Commitment/Consistency; Foot-in-the-Door; Reciprocity/Reciprocal concessions; Door-in-the-Face; Binge drinking; Psychology, Social (0451)